2018
DOI: 10.1111/jgs.15235
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Emergency Department Innovations: Transitional Care Nurses and Hospital Use

Abstract: INTERVENTION:The intervention was first TCN contact. Controls never saw a TCN during the study period. MEASUREMENTS: We examined sociodemographic and clinical characteristics associated with TCN use and outcomes. The primary outcome was inpatient admission during the index ED visit (admission on Day 0). Secondary outcomes included cumulative 30-day admission (any admission on Days 0-30) and 72-hour ED revisits. RESULTS: A TCN saw 5,930 (10%) individuals, 42% of whom were admitted. After accounting for observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 42 publications
(51 reference statements)
2
111
0
Order By: Relevance
“…The field of geriatric emergency medicine continues to evolve rapidly. For instance, between the conclusion of our search and the peer review process of this article, an array of studies were published including a review of self‐defined geriatric EDs, a nurse transition intervention, and a pragmatic trial of an Australian‐based geriatric ED . Ongoing research is likely to result in additional articles in the near future, as evidenced by scientific abstracts presented at recent scientific meetings.…”
Section: Discussionmentioning
confidence: 99%
“…The field of geriatric emergency medicine continues to evolve rapidly. For instance, between the conclusion of our search and the peer review process of this article, an array of studies were published including a review of self‐defined geriatric EDs, a nurse transition intervention, and a pragmatic trial of an Australian‐based geriatric ED . Ongoing research is likely to result in additional articles in the near future, as evidenced by scientific abstracts presented at recent scientific meetings.…”
Section: Discussionmentioning
confidence: 99%
“…29,39,40 Using an Observation Unit provides a setting and time for these assessments to occur without interrupting the flow of medical care in the ED. Comprehensive Geriatric Assessment (CGA) is a comprehensive and multidisciplinary review of social and health issues including cognitive function in order to develop a coordinated and integrated plan for treatment and longterm follow up.…”
Section: What Can the Ed Do?mentioning
confidence: 99%
“…Although generally time consuming, and considered by some an oxymoron for the ED environment, models have been developed for this to occur in the ED itself or in an ED co-located unit, such as an Observation Unit or Frailty Unit. 29,39,40 Using an Observation Unit provides a setting and time for these assessments to occur without interrupting the flow of medical care in the ED. [41][42][43] There is an experience with a co-located Emergency Frailty Unit that facilitates CGA including geriatric assessment and has been shown to reduce ongoing admissions and representations to ED.…”
Section: What Can the Ed Do?mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study of a Transitional Care Nurse model, in which an ED nurse was trained to facilitate care transitions for older adults, reduced subsequent inpatient admissions by 5%À16%. 9 However, other studies have shown mixed results on the impacts of nurse-led interventions, demonstrating there is still more work to do to understand the best models of care. 10 As frontline providers, nurses offer a unique perspective on caring for older adults in the ED.…”
mentioning
confidence: 99%